Elderly Self-Help Groups: A Community-Based Education and Peer Support Program for Hypertension Control, Supporting SDG 3 on Health and Well-being - Heni Kusumawardani Lita; Hasra Azera; Triyanto Endang; Iskandar Asep (E3S Web of Conferences)
The primary cause of death for people worldwide is hypertension. Heart disease, stroke, and even death can result from uncontrolled hypertension. Researchers are encouraged by this situation to create an integrated education model based on the Self-Help Group (SHG) method of instruction. This pressing global health issue aligns with the United Nations' Sustainable Development Goals (SDGs), particularly Goal 3, which seeks to ensure healthy lives and promote well-being for all at all ages. This study sought how community-based education and peer support, spearheaded by Eldery's SHG, could help manage hypertension. The design used a quasi-experiment design with quantitative research methods. The study's sample consisted of the elderly self-help group in Banyumas Regency, a rural district of Indonesia, in 2024. Sixty-eight respondents were gathered using a probability sampling technique combined with primary random sampling. This analysis included A control group in the quasi-experimental pre-post test paradigm. An SHG intervention was given for this investigation. The paired and independent t-tests were utilised in the analysis. According to the study's findings, the SHG significantly reduced older adults's blood pressure compliance for both the systole and diastole of their blood pressure (p = 0.004) and p = 0.003). The study's findings are anticipated to be used in community-based education and other subject areas.